A Igreja Apostólica (da santa vó Rosa): entre rupturas e continuidades, a criação de um novo ascetismo - São Paulo, 1954-1970 - Santos, Pablo Henrique Costa (2018)
This work develops an analysis of moral discipline of the Apostolic Church (of saint vó Rosa), an institution organized from 1954, in Sao Paulo, from the Pentecostal movement and by the religious leadership of Mrs. Rosa who became recognized as a saint by the church after her death. The moral codes of this church are considered sacred laws, but demonstrates in its organization strategies that support a social and cultural power. The set of codes of conduct suggests a specific way of life for salvation. The laws promote the management of bodies and behaviors in the time when there were signs of degeneration, the time of the end. The rules would then be an option of regeneration. Sociability, subjectivity and the way members interact with the "world" are constituted according to what the church preaches. Along with this issue, it is intended to go through discussions that circulate around religious movements of the twentieth century and even resort to the long-standing Christian tradition. Thematics such the end times, Holiness, prophecy, Charisma and magic will also be evoked. The sources used in this research were the three books of the institution: O Evangelho do Reino dos Céus, o Espírito Santo de Deus e o Consolador, O Consolador nos Tempos do Fim. A number of official internal bulletins were also verified, in addition to the doctrine summary texts available on the institution's website and the transcription of preaching from the main pastors of the church. The methodology consisted in the analysis of the discourses from the historical-critical perspective, but in line with the phenomenological. In addition it was used the comparative method and participant observation of religions. The intention is to surround these discourses, punctuate permanences and ruptures with other religious traditions and identify their strategies of power support.